How to get rich on the Oregon Trail : my adventures among cows, crooks & heroes on the road to fame and fortune : writing journal of--Master William Reed : Portland, Oregon 1852 - Olson, Tod (National Geographic, 2009)
This whimsical recounting of one family's journey to their new homestead will give readers an appreciation of the hardships faced by all those who signed up for the great migration. These include hunger, thirst, sickness, hostile American Indians, and even deceit and thievery on the part of fellow travelers. The book also shows the ingenuity, skill, and trickery used to overcome such challenges.